(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Texts written in Iberian language are often found engraved on silverware (silver bowls, vessels). The purpose of this contribution is on the one hand to analyze questions of method as applied to the study of these inscriptions, and on the other to report the innovation brought about with the use of a dissecting microscope (a binocular magnifying glass) to examine the texts. Finally, a case-study is presented: a well-known piece, generally called El Alcornocal, preserved at the Museo Arqueológico Nacional.